Relationship between T regulatory cell levels (CD4 + CD25 + CD127- T cells) and the presence of autoantibodies in adult patients with selective IgA deficiency (Annals of Medical Research, 2021)
Aim: Selective immunoglobulin A (sIgA) deficiency is the most common primary immunodeficiency. Individuals with selective IgA deficiency are generally considered to be asymptomatic. In some patients, autoimmune diseases have been reported. Regulatory T cells (T reg) are a group of cells that play a key role in preventing autoimmunity.Material and Methods: 28 patients with selective IgA deficiency and a control group consisting of 15 individuals of similar age and sex were included in the study.Results: Serum IgA levels were lower in patients with sIgA deficiency (p 0.001). There was no difference between the two groups in term of the rate of Treg cells (p: 0.562 and p: 0.873). There was at least one autoantibody positivity in 19 (67.8%) patients with sIgA deficiency and 4 (26.7%) in the control group. The most common positive autoantibody was ANA in both groups. Serum IgG and IgG1 levels were significantly higher in sIgA deficiency patients with autoantibody than in the other group (p: 0.004 and p: 0.004) The relationship between presence of autoantibodies and Treg cell levels in patients with sIgA deficiency was not statistically significant (p: 0.199). The regression analysis showed that the IgG level (OR: 1.594, 95% CI: 1.096-2.319, p: 0.015) was an independent predictor for the presence of autoantibodies.Conclusion: The findings of our study are important as they are the first evaluation in adult sIgA deficient patients. Further studies are required to shed light on this issue in order to evaluate more patients with sIgA deficiency with autoimmunity.
Keywords: Selective IgA deficiency; T regulatory cells; autoantibodies